Severe Acute Respiratory Syndrome Coronavirus 2-Induced Neurological Complications - Yu, Shijia; Yu, Mingjun (Frontiers in Cell and Developmental Biology, 2020)
Our review aims to highlight the neurological complications of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and the available treatments according to the existing literature, discussing the underlying mechanisms. Since the end of 2019, SARS-CoV-2 has induced a worldwide pandemic that has threatened numerous lives. Fever, dry cough, and respiratory symptoms are typical manifestations of COVID-19. Recently, several neurological complications of the central and peripheral nervous systems following SARS-CoV-2 infection have gained clinicians’ attention. Encephalopathy, stroke, encephalitis/meningitis, Guillain-Barré syndrome, and multiple sclerosis are considered probable neurological signs of COVID-19. The virus may invade the nervous system directly, or induce a massive immune inflammatory response via a “cytokine storm”. Specific anti-viral drugs are still under study. To date, immunomodulatory therapies and supportive treatment are the predominant strategies. In order to improve the management of COVID-19 patients, it is crucial to monitor the onset of new neurological complications, and to explore drugs/vaccines targeted against SARS-CoV-2 infection.